Nature-Related Financial Risks and Their Emerging Role in Banking Regulation and Sustainable Investment - Ariawan Ariawan; Nabila Tijani Tharifah; Anggun Wida Prawira; Sahal Hanafi (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
This study examines the transmission channels of nature related financial risks into the global banking sector and sustainable investment portfolios through a non linear macroeconomic modeling framework. Utilizing panel vector autoregression and structural equation modeling on secondary data from systemically important commercial banks, the paper evaluates the compounding impacts of physical ecosystem shocks and macroprudential regulatory transitions. The empirical results reveal that localized physical vectors, such as hydrological stress and soil degradation, function as leading indicators for escalating non performing loan ratios and deteriorating asset qualities. Furthermore, sudden regulatory realignments and capital requirement adjustments generate material transition pressures that amplify structural frictions within institutional business models. The findings indicate that current generalized biodiversity screening tools fail to capture site specific project risks, thereby inflating portfolio risk exposures. This research concludes that safeguarding macrofinancial stability requires a comprehensive structural reorientation, shifting from carbon centric perspectives toward unified double materiality prudential frameworks that enforce biodiversity transparency and effectively mobilize private capital toward verifiable ecological restoration.